Fatigue-Related Cognitive Performance in Oil and Gas Operations A Review from an Applied Data Science Perspective - Hidayah Nurul Hasanah Zen; Ridho Rahmadi; Zaenal Abidin; Allen Haryanto Lukmana (Journal of Petroleum and Geothermal Technology, 2026)
Fatigue and environmental stressors are critical contributors to reduced concentration and safety risks among onshore and offshore oil and gas engineers. This review aims to synthesize existing research on the detection of reduced concentration levels related to fatigue and environmental factors, comparing onshore and offshore working conditions. Furthermore, this review suggests practical solutions for industry application. In this study, a structured literature review was conducted using quantitative, qualitative, and technology-based studies addressing fatigue detection, management strategies, and psychosocial and organizational risk factors across diverse operational contexts. The results indicate that offshore engineers experience higher fatigue prevalence due to shift work, isolation, and harsh environmental conditions, while onshore engineers are more affected by occupational monotony and limited social support. The reviewed studies indicate that fatigue detection approaches commonly combine subjective self-reports with physiological and performance-based indicators; however, their validation and standardization remain limited. Multidimensional interventions integrating sleep management, mental health support, and organizational reforms show potential but lack robust empirical evaluation. In conclusion, the review highlights the need for standardized, integrative fatigue assessment frameworks and context-specific fatigue risk management strategies to improve cognitive performance, safety, and well-being in both onshore and offshore oil and gas operations.